Market Potential and Global Growth over the Long Twentieth Century - David S. Jacks; Dennis Novy (Center for Economic Studies and ifo Institute (CESifo), 2018)
We examine the evolution of market potential and its role in driving economic growth over the long twentieth century. Theoretically, we exploit a structural gravity model to derive a closed-form solution for a widely-used measure of market potential. We are thus able to express market potential as a function of directly observable and easily estimated variables. Empirically, we collect a large dataset on aggregate and bilateral trade flows as well as output for 51 countries. We find that market potential exhibits an upward trend across all regions of the world from the early 1930s and that this trend significantly deviates from the evolution of world GDP. Finally, using exogenous variation in trade-related distances to world markets, we demonstrate a significant causal role of market potential in driving global income growth over this period.
Keywords: F10; N70; 330; economic geography; market potential; structural gravity; trade costs